The Majorana Demonstrator readout electronics system. (1st May 2022) - ,; Abgrall, N.; Amman, M.; Arnquist, I.J.; Avignone , F.T.; Barabash, A.S.; Barton, C.J.; Barton, P.J.; Bertrand, F.E.; Bhimani, K.H.; Bos, B.; Bradley, A.W.; et al.
Abstract: The Majorana Demonstrator comprises two arrays of high-purity germanium detectors constructed to search for neutrinoless double-beta decay in 76 Ge and other physics beyond the Standard Model. Its readout electronics were designed to have low electronic noise, and radioactive backgrounds were minimized by using low-mass components and low-radioactivity materials near the detectors. This paper provides a description of all components of the Majorana Demonstrator readout electronics, spanning the front-end electronics and internal cabling, back-end electronics, digitizer, and power supplies, along with the grounding scheme. The spectroscopic performance achieved with these readout electronics is also demonstrated.